Spontaneous Termination of Spinal Myoclonus after Spinal Anesthesia: A Case Report - Puetpaiboon, Asamaporn; Amornpojnimman, Thanyalak (Journal of Health Science and Medical Research, 2023)
Spinal myoclonus following neuraxial anesthesia isextremely rare. Herein, wereport onacase of spinal myoclonus after spinal anesthesia for elective colpocleisis with perineorrhaphy, in a 71-year-old woman. Sudden, brief, repetitive, and rhythmic hyperkinetic movement in both legs developed two hours after spinal injection with hyperbaric bupivacaine; which then spontaneously resolved after 45 minutes without leaving any neurologic deficit.